An Empirical Study on the Perception of Consumers about Green Products in Delhi - Trivedi, Prachi; Sharma, Meghna (International Journal of Engineering and Technology, 2018)
Green is the talk of the town. Every other day new strategies and technologies are being invented to fight the deadliest consequences of environmental degradation. The pace at which our Planet is being exploited and environmental problems are increasing, Green Marketing and Green Products have become a necessity. But this â€˜green conceptâ€™ will only be successful when the awareness level will be high and perception is positive. In this paper perception of consumers about green products in Delhi is being studied. Is the overall perception negative, positive or neutral? Do they appreciate the packaging of green products? Or is there any correlation between perception and various demographic variables of consumers? All these questions are answered in this paper with detailed analysis. Structured and undisguised form of questionnaire was prepared which was distributed to 120 respondents out of which 106 were found to be usable. Any sample above 30 is considered large. Statistical tools like mode, median, frequency distribution, Kruskal-Wallis and One way ANOVA are used to test the hypotheses. This paper will be beneficial to other researchers to get the insight of consumersâ€™ perception about green products, to companies in making the right strategies and policies according to consumer perception and to other organization and institutes who are interested in studying the consumer behaviour regarding Green Products.Â Â